Actuarial risk management of investment guarantees in life insurance - Bekker, Kobus Nel (University of the Free State, 2010)
Investment guarantees in life insurance business have generated a lot of research in recent years due to the earlier mispricing of such products. These guarantees generally take the form of exotic options and are therefore difficult to price analytically, even in a simplified setting. A possible solution to the risk management problem of investment guarantees contingent on death and survival is proposed through the use of a conditional lower bound approximation of the corresponding embedded option value. The derivation of the conditional lower bound approximation is outlined in the case of regular premiums with asset-based charges and the implementation is illustrated in a Black-Scheles-Merton setting. The derived conditional lower bound approximation also facilitates verifying economic scenario generator based pricing and valuation, as well as sensitivity measures for hedging solutions.
Thesis (Ph.D. (Mathematical Statistics))--University of the Free State, 2010
Keywords: Life insurance; Life insurance -- Mathematics; Life insurance -- Risk assessment; Insurance -- Statistics